2020
DOI: 10.3390/antibiotics9100647
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Colistin versus Colistin Plus Meropenem for the Treatment of Carbapenem-Resistant Acinetobacter baumannii in Critically Ill Patients: A Propensity Score-Matched Analysis

Abstract: Carbapenem-resistant Acinetobacter baumannii (CRAB), an important nosocomial pathogen, occurs particularly in the intensive care unit (ICU). Thus, the aim of this study was to compare the efficacy and safety of documented treatment with colistin monotherapy versus colistin plus meropenem in critically ill patients with CRAB infections at Chiang Mai University Hospital (CMUH). We conducted a retrospective cohort study of critically ill patients with CRAB infections in an ICU from 2015 to 2017, who received coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…The study also found that the addition of meropenem to colistin caused a reduction in 30-day mortality, higher clinical and microbiological responses, and did not increase nephrotoxicity compared to colistin monotherapy. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also found that the addition of meropenem to colistin caused a reduction in 30-day mortality, higher clinical and microbiological responses, and did not increase nephrotoxicity compared to colistin monotherapy. 28 …”
Section: Discussionmentioning
confidence: 99%
“…27 The study also found that the addition of meropenem to colistin caused a reduction in 30-day mortality, higher clinical and microbiological responses, and did not increase nephrotoxicity compared to colistin monotherapy. 28 To reduce the incidence of PMB-associated nephrotoxicity, physicians and pharmacists could collaborate on the rational use of PMB. They should cooperate in developing more precise treatment plans for patients with CR-GNB infections: appropriate PMB dosage, safe and reasonable drug combinations, and drug adjustment after nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“… 9 A study investigated the colistin versus colistin plus meropenem for the treatment of CRAB in critically ill patients, and found that the meropenem plus colistin regimen caused a reduction in 30-day mortality, higher clinical and microbiological responses, and did not increase nephrotoxicity compared to colistin monotherapy. 22 Colistin combination with vancomycin was not necessary for the management of critically ill patients infected with CRAB. 23 In patients with septic shock, the mean arterial pressure and ventilator use are related to mortality, 24 which is consistent with the conclusions of the clinical efficacy analysis in our study; that is, mechanical ventilation, use of vasoactive drugs, respiratory diseases, hepatobiliary diseases, and the number of CR-GNB infections were related to clinical failure of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among several proposed therapies for the further treatment of GNB infections [ 42 , 43 ], a combination of colistin with other antibiotics is considered a potential approach associated with overcoming the outer membrane permeability barrier, a broader antibacterial spectrum, synergistic effects and reduced risk for emerging resistance during therapy [ 20 , 44 , 45 ]. In addition, many studies have demonstrated that, in contrast to monotherapy, combination therapy may enhance antimicrobial effects and provide synergism [ 46 , 47 , 48 , 49 , 50 ]. In this study, the NCL179 + colistin combination showed synergistic activity against all tested GNB pathogens, including colistin-resistant A. baumannii and E. coli isolates, comparable to other synergy reports of combining colistin with other antibiotics [ 44 , 46 , 51 ].…”
Section: Discussionmentioning
confidence: 99%